2011
DOI: 10.1007/s11244-011-9700-3
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Kinetics of the Fischer–Tropsch Synthesis on Cobalt Catalysts Based on H-Assisted CO Activation

Abstract: A complete mechanistic kinetic model of the Fischer-Tropsch synthesis (FTS) over a Co/Al 2 O 3 stateof-the-art catalyst is developed here under conditions relevant to industrial operation. On the basis of the most recent findings on the reaction mechanism, here described according to the H-assisted CO dissociation theory and the alkyl chain growth mechanism, and on the basis of the latest indications available on the rate determining step involved in the CO activation process, rate expressions for all the step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
118
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(134 citation statements)
references
References 40 publications
15
118
1
Order By: Relevance
“…S6, ESI †). In line with other reports, 16 the methane level, higher than that of the ASF distribution, implies that a secondary reaction of CO hydrogenation takes place (in addition to FTS) for all the Co catalysts. As compared to Co/SiO 2 , the higher CH 4 molar fraction obtained over Co/zeolite catalysts (see inset in Fig.…”
supporting
confidence: 92%
“…S6, ESI †). In line with other reports, 16 the methane level, higher than that of the ASF distribution, implies that a secondary reaction of CO hydrogenation takes place (in addition to FTS) for all the Co catalysts. As compared to Co/SiO 2 , the higher CH 4 molar fraction obtained over Co/zeolite catalysts (see inset in Fig.…”
supporting
confidence: 92%
“…There is a general consensus that the reaction proceeds through a polymerization-like scheme where the monomeric building block is formed on the catalyst surface and is inserted in a growing chain [1]. This has led to the development of various microkinetic models for Co catalyzed FTS [15][16][17][18][19][20][21][22][23][24][25][26]. Klinke et al [16] developed a microkinetic model based on direct CO dissociation and chain growth by inserting CHx species.…”
Section: Introductionmentioning
confidence: 99%
“…The UBI-QEP [27][28][29] method was applied for the calculation of chemisorption enthalpies and activation energies [17]. The CO dissociation has been assessed by Visconti et al [18,19] in two consecutive papers and showed that CO dissociation is, most…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Although this assumption is fairly relevant for many catalytic systems, several reports deal with non-ASF product distributions. 24 Dissimilar sites or (parallel) growth mechanisms in one catalyst, 25 altered α values in different carbon number regions, 26 and the so-called "bifunctional catalysts" that represent a "break" in ASF plot 27 are among such exceptions.…”
Section: Discussionmentioning
confidence: 99%